Perubahan Status Nabi Dari Makkah ke Madinah Perspektif Tafsir Nuzuli: Telaah Pemikiran Tafsir Izzat Darwazah - Permana, Fadhila Sidiq; Rafsanjani, Anugerah Zakya (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2024)
Abstract: The research aims to investigate the relevance of the implementation of the Qur'an within the framework of daily life. The Qur'an, as a divine revelation delivered to the Prophet Muhammad SAW through the angel Gabriel, serves as a foundational source of knowledge in Islam. This study employs a literature review methodology, analyzing diverse reference materials through keywords such as